Nature of changes in adrenocortical function in chronic hyperleptinemic female rats - Perelló, Mario Carlos (2004)
Neonatal treatment of rats with monosodium l-glutamate, which destroys hypothalamic arcuate nucleus neuronal bodies, induces several metabolic abnormalities; as a result, rats develop a phenotype of pseudoobesity. This study was designed to explore, in the monosodium l-glutamate-treated female rat, the influence of chronic hyperleptinemia on adrenal cortex functionality. For this purpose, we evaluated in control and hypothalamic-damaged rats: (a) in vivo and in vitro adrenocortical function, (b) adrenal leptin receptor immunodistribution and mRNA expression, and (c) whether the inhibitory effect of leptin on adrenal function remains. Our results indicate that, compared to normal counterparts, pseudoobese animals displayed (1) hyperadiposity, despite being hypophagic and of lower body weight, (2) in vivo and in vitro enhanced adrenocortical response to ACTH stimulation, (3) an in vitro adrenal fasciculata-reticularis cell hyper-sensitivity to ACTH stimulus, (4) hyperplasia of their adrenal zona fasciculata cells, and (5) adrenal fasciculata-reticularis cell refractoriness to the inhibitory effect of leptin on ACTH-stimulated glucocorticoid production due, at least in part, to decreased adrenal leptin receptor expression. These data further support that increased hypothalamo-pituitary-adrenal axis function, in the adult neurotoxin-lesioned female rat, is mainly dependent on the development of both hyperplasia of adrenal zona fasciculata and adrenal gland refractoriness to leptin inhibitory effect. Our study supports that adrenal leptin resistance could be responsible, at least in part, for enhanced glucocorticoid circulating levels in this phenotype of obesity.